Spiral microchannel with ordered micro-obstacles for continuous and highly-efficient particle separation. Issue 21 (4th October 2017) - Shen, Shaofei; Tian, Chang; Li, Tianbao; Xu, Juan; Chen, Shu-Wei; Tu, Qin; Yuan, Mao-Sen; Liu, Wenming; Wang, Jinyi
Abstract : We present a microfluidic system containing a spiral channel interspersed with micro-obstacles, which allows secondary flow acceleration for enhancing particle separation. Abstract : Controllable manipulation of fluid flow is crucial for efficient particle separation, which is associated with plenty of biomedical and industrial applications. Microfluidic technologies have achieved promising progress in particle positioning depending on inertial force with or without the help of the Dean effect. Herein, we describe an inertial microfluidic system containing a spiral microchannel for various highly efficient particle separations. We demonstrated that Dean-like secondary flow can be regulated by geometric confinement in the microchannel. On the introduction of a library of micro-obstacles into the spiral microchannels, the resulting linear acceleration of secondary flow can be applied to remarkably enhance particle focusing in time and space. Further, multiple separating and sorting manipulations of particles including polymeric particles, circulating tumor cells, and blood cells, can be successfully accomplished in the dimension-confined spiral channels in a sheathless, high-throughput (typically 3 ml min −1 ), long-term (at least 4 h), and highly-efficient (up to 99.8% focusing) manner. The methodological achievement pointing to ease-of-use, effective, and high-throughput particle manipulations is useful for both laboratory and commercial developments of microfluidic systems in life and material sciences.